Empathy: Assessment Instruments and Psychometric Quality – A Systematic Literature Review With a Meta-Analysis of the Past Ten Years - Lima, Felipe Fernandes de; Osório, Flávia de Lima (Frontiers in Psychology, 2021)
Objective: to verify the psychometric qualities and adequacy of the instruments available in the literature from 2009 to 2019 to assess empathy in the general population. Methods: The following databases were searched: PubMed, PsycInfo, Web of Science, Scielo, and LILACS using the keywords “empathy” AND “valid*” OR “reliability” OR “psychometr*”. A qualitative synthesis was performed with the findings, and meta-analytic measures were used for reliability and convergent validity. Results: 50 studies were assessed, which comprised 23 assessment instruments. Of these, 13 proposed new instruments, 18 investigated the psychometric properties of instruments previously developed, and 19 reported cross-cultural adaptations. The Empathy Quotient, Interpersonal Reactivity Index, and Questionnaire of Cognitive and Affective Empathy were the instruments most frequently addressed. They presented good meta-analytic indicators of internal consistency (reliability, generalization meta-analyses (Cronbach’s alpha): 0.61 to 0.86), but weak evidence of validity (weak structural validity; low to moderate convergent validity (0.27 to 0.45)). Few studies analyzed standardization, prediction, or responsiveness for the new and old instruments. The new instruments proposed few innovations, and their psychometric properties did not improve. In general, cross-cultural studies reported adequate adaptation processes and equivalent psychometric indicators, though there was a lack of studies addressing cultural invariance. Conclusions: Despite the diversity of instruments assessing empathy and the many associated psychometric studies, there remain limitations, especially in terms of validity. Thus far, we cannot yet nominate a gold-standard instrument.